NMR studies of methane and hydrogen in microporous materials - Hamida, J.A.; Tang, Y.; Sullivan, N.S.; Ji, Y. (Физика низких температур, 2016)
We review the results of nuclear magnetic resonance studies of the molecular dynamics of the quantum gases
HD and CH₄ adsorbed in the cages of microporous structures. Measurements of the variation of the nuclear spinlattice
and nuclear spin-spin relaxation times with temperature provide detailed information about the translational
and rotational dynamics of the adsorbed molecules over a wide temperature range.